Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Lin, Ye-Jie (Zootaxa, 2020)
Tibetyrus formicarius Yin & Lin, gen. et sp. nov., a new myrmecophilous genus and species of the pselaphine tribe Tyrini, is described from southeastern Xizang, China. Three adults were collected in nests of a Formica ant species (Hymenoptera: Formicidae) at an altitude of 3,485 m. Tibetyrus is similar to Megatyrus Hlaváč & Nomura in sharing the basally pedunculate maxillary palpi that lack an apical cone on the fourth palpomeres. Nevertheless, it can be readily separated from the latter and all other genera of the tribe by its unique suite of morphological features as well as a highly recognizable habitus.